2019
DOI: 10.1021/acsnano.9b06505
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Conductance through Graphene: Assessing Its Applicability as a Proton Selective Membrane

Abstract: Inspired by recent reports on possible proton conductance through graphene, we have investigated the behavior of pristine graphene and defect engineered graphene membranes for ionic conductance and selectivity with the goal of evaluating a possibility of its application as a proton selective membrane. The averaged conductance for pristine chemical vapor deposited (CVD) graphene at pH1 is ∼4 mS/cm 2 but varies strongly due to contributions from the unavoidable defects in our CVD graphene. From the variations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
41
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 74 publications
8
41
2
Order By: Relevance
“…In any case, the estimated (sub)nanometer pore geometry from this simple model indicates that the local H + transmission sites through the macroscopic graphene|Nafion membrane likely coincide with relatively-rare atomic-scale defects (naturally-occurring or introduced, vide infra) in the graphene overlayer film, consistent with some previous reports. [15][16][17][18] A summary of example G/A values reported in previous studies, alongside the graphene preparation method and size of the measured membrane is reported in the SI, Section S8. The G/A values previously reported for macroscopic graphene|Nafion membranes varies over several ordersof-magnitude (≈0.09 to 30 S cm −2 , reported 11,12,19 ), which is perhaps unsurprising, given that macroscopic defects such as pinholes, cracks and other imperfections are known to be present.…”
Section: Estimating the Dimensions Of The Proton-conducting Sites H + Conduction Through Local Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, the estimated (sub)nanometer pore geometry from this simple model indicates that the local H + transmission sites through the macroscopic graphene|Nafion membrane likely coincide with relatively-rare atomic-scale defects (naturally-occurring or introduced, vide infra) in the graphene overlayer film, consistent with some previous reports. [15][16][17][18] A summary of example G/A values reported in previous studies, alongside the graphene preparation method and size of the measured membrane is reported in the SI, Section S8. The G/A values previously reported for macroscopic graphene|Nafion membranes varies over several ordersof-magnitude (≈0.09 to 30 S cm −2 , reported 11,12,19 ), which is perhaps unsurprising, given that macroscopic defects such as pinholes, cracks and other imperfections are known to be present.…”
Section: Estimating the Dimensions Of The Proton-conducting Sites H + Conduction Through Local Transmissionmentioning
confidence: 99%
“…To contextualize the results reported herein, the density of defects (defects μm −2 ) required to achieve the reported G/A values is also calculated, assuming an individual defect resistance of 170 MΩ•defect. As shown in Table S1, the lower end of defect densities (0.005 defects μm −2 ), obtained from high-quality, small-area graphene membranes produced by exfoliation (3 mS cm −2 , reported 5 ) or CVD (4 mS cm −2 , reported 18 ) is in good agreement with the number of defects detected on the more pristine areas of the graphene|Nafion membrane, with values of 0.007, 0.02 and 0.008 defects μm −2 calculated for Figure 2a, Figure 3a and Figure 4a-ii (assuming 1 defect/pixel), respectively. To match the highest-performing defect-engineered graphene membranes (G / A values of up to ≈1000 mS cm −2 , reported 17 ), the density of defects would need to increase by >2 orders-of-magnitude (assuming a constant defect resistance of 170 MΩ•defect) up to ca.…”
Section: Estimating the Dimensions Of The Proton-conducting Sites H + Conduction Through Local Transmissionmentioning
confidence: 99%
“…It has been reported that the graphene sheets consisted of interatomic openings in their electron density distribution (ca. 0.064 nm) [40]; these extremely small pores correlated well with the effective proton size, but are too small for other large ions to penetrate [36]. Both pristine graphene and nanoporous graphene (either with intrinsic atomic-scale defects or intentionally engineered defects) are being continuously studied as potential membranes for gas separation and purification [41][42][43][44][45][46][47], desalination [48][49][50][51][52][53], methanol crossover mitigation [54,55], and CO 2 post-combustion capturing [56].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental findings have established exclusive high proton transmission through single-layer graphene (ca. 0.5-0.78 eV [34,35], energy barrier) while simultaneously blocking transmission of other species [36][37][38][39]. It has been reported that the graphene sheets consisted of interatomic openings in their electron density distribution (ca.…”
Section: Introductionmentioning
confidence: 99%
“…These G/A values reportedly represented the "intrinsic proton conductivity" of the studied 2D crystals (i.e., through-plane proton conduction), 5,12 challenging the widely-accepted notion that pristine graphene is impermeable to all atoms, ions and molecules under ambient conditions. 13,14 Subsequent studies by a number of research groups [15][16][17][18] have suggested that selective H + transport may be facilitated at defect sites (naturally-occurring 15,16 or introduced 17,18 ) that are likely separate from the sites that facilitate the transport of other ions (i.e., pores in nanoporous graphene, vide supra). 8,11,19 Since the initial report, 5 there has been increasing interest in the scaling up of proton-selective membranes based on graphene and related 2D materials.…”
mentioning
confidence: 99%